Preparation of dry flowable formulations of Clonostachys rosea by spray drying and application for Sclerotinia sclerotiorum control - Hong-qu WU; Li-li SUN; Fang LIU; Zhi-ying WANG; Chuan-wang CAO (Journal of Integrative Agriculture, 2018)
A dry flowable formulation of Clonostachys rosea with fungicidal activity against Sclerotinia sclerotiorum was prepared by spray drying. The formulation was optimized by a four-factor, three-level orthogonal experiment to screen inert ingredients and spray-drying conditions. The optimal dry flowable formulation of C. rosea included 30% C. rosea (ratio of conidia powder and its fermentation broth is 1:3), 3% Morwet EFW, 4% K12, 10% Morwet D425, 9% sodium salt of polynaphthalene sulphonic acid (NNO), 5% croscarmellose sodium, 5% (NH4)2SO4, 0.5% carboxymethyl cellulose sodium (CMC-Na), 1% oxalic acid and palygorskite (carrier) up to 100%. The formulation exhibited good physical characteristics, such as high dispersibility, viability and a long shelf life. Plate antagonism tests and pot trials indicated that the dry flowable formulation was very effective against S. sclerotiorum, with control efficiency of up to 88.30%. This dry flowable formulation of C. rosea is a new potential commercial fungicide for spray drying to control S. sclerotiorum.